2023
DOI: 10.1002/tea.21899
|View full text |Cite
|
Sign up to set email alerts
|

How do thinking styles and STEM attitudes have effects on computational thinking? A structural equation modeling analysis

Haozhe Jiang,
A. Y. M. Atiquil Islam,
Xiaoqing Gu
et al.

Abstract: Computational thinking (CT) is vital for success in numerous domains. However, the nature, definition, and scope of CT are ill‐defined, and research on how best to develop CT is very limited. This study focused on how thinking styles and STEM attitudes have effects on computational thinking. Using a proportionate stratified random sampling procedure, 1195 students from two universities were surveyed. A structural equation modeling analysis showed that students' thinking styles and STEM attitudes directly predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 132 publications
0
5
0
Order By: Relevance
“…STEM education has been advocated and intensively implemented all over the world over the past years [ 12 , 57 , 63 , 68 ]. However, it is reported that there is a severe shortage of qualified STEM teachers around the world [ 69 , 70 , 71 ], which has hindered the implementation of STEM education reforms [ 12 , 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…STEM education has been advocated and intensively implemented all over the world over the past years [ 12 , 57 , 63 , 68 ]. However, it is reported that there is a severe shortage of qualified STEM teachers around the world [ 69 , 70 , 71 ], which has hindered the implementation of STEM education reforms [ 12 , 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the organizational level, human resources managers could encourage a supportive internal workplace by implementing a suitable code of conduct and arranging meetings to promote and cultivate a civil culture of learning and collaboration. In recent years, many countries have released a lot of policies to support STEM teaching [ 12 , 57 , 63 , 68 , 74 , 75 ]. Schools should help novice STEM teachers realize these policies so that novice STEM teachers can perceive that what they are doing is supported by the governments and societies [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, a certain amount of caution is still needed when generalizing our findings. Meanwhile, considering the huge development gap between coastal and inland provinces in China (Jiang et al 2021;Jiang et al 2024), it should be acknowledged that teachers in different regions may have different AI resources, knowledge and learning opportunities. In the future, regional comparisons are needed to understand the differences of behavioral intentions to learn AI among teachers in different regions.…”
Section: Discussionmentioning
confidence: 99%